Analyzing the Mission and Strategy of Berani Hijrah Community on Developing Islamic Religious Education - Misbahul Munir; Cahaya Cahaya; Mulyana Abdullah; Jenuri Jenuri; Abdul Rahim Karim (Fakultas Tarbiyah Institut Agama Islam Sunan Giri Ponorogo, 2023)
The main purpose of this research is to analyze the mission and strategies carried out by the Berani Hijrah Community (BHC) on developing Islamic religious education for the younger generation. This research is qualitative with a phenomenological approach. The subject of the study was a community that dared to migrate to Dusun IV, Limau Manis, Tanjung Morawa, Deli Serdang, and North Sumatra-research data in the form of BHC missions and strategies in developing Islamic religious education. Data sources are obtained from all community members who dare to migrate. Observation, interviews, and documentation carry out data collection techniques. At the same time, data analysis is carried out by data reduction, data presentation, and conclusions. This research concludes that the courageous migration community employs various strategies, including bringing in popular religious teachers (ustadz) whom teenagers like to generate greater enthusiasm in delivering youth-oriented religious lectures. The strategies also involve increasing parental awareness and involvement, developing a relevant curriculum, establishing study groups and discussions, and organizing social and humanitarian activities.